"We are responsible for the violence, and prevention is up to us": a qualitative study of perceived risk factors for gender-based violence among Ethiopian university students - Michelle R. Kaufman; Ashlie M. Williams; Graziele Grilo; Christina X. Marea; Fasil Walelign Fentaye; Lakew Abebe Gebretsadik; Shifera Asfaw Yedenekal (BMC, 2019)
Abstract Background There is a high prevalence of gender-based violence (GBV) victimization among young Ethiopian women, including in universities, where female enrollment is low but growing. Understanding factors contributing to GBV in this context and students' perspectives on gender, relationships, and interpersonal violence is essential to creating effective interventions to prevent GBV and support female students' rights and wellbeing. Methods In-depth interviews (IDIs) and focus group discussions (FGDs) were held with male and female students (male IDI n = 36, female IDI n = 34, male FGD n = 18, female FGD n = 19) and faculty and staff (FGD n = 19) at two Ethiopian universities. Audio recordings were transcribed and translated into English. Transcripts were coded thematically to identify key factors contributing to GBV and provide narratives of students' experiences. Results GBV against female students was a salient issue, including narrative accounts of harassment, intimidation, and physical and sexual violence on the university campuses and the towns in which they are located. Reported risks for GBV included receiving academic support from male peers, exercising agency in relationship decision-making, having a negative self-concept, belief in stereotypical gender expectations, and engaging in transactional sex and/or substance use. While students recognized these risk factors, they also suggested GBV may be the result of females' "improper" behavior, attire, use of males for personal gain, or personal failure to prevent violence. Conclusions GBV is a serious issue in these two Ethiopian universities, creating a tenuous learning environment for female students. Programs are needed to address areas of vulnerability and negative attitudes toward female students in order to decrease female victimization.